2004
DOI: 10.1097/00075198-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Is it wise not to think about intraabdominal hypertension in the ICU?

Abstract: The answer is that it is unwise not to measure intraabdominal pressure in the ICU or even not to think about it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 73 publications
1
98
0
17
Order By: Relevance
“…Some papers have demonstrated that a persistent splanchnic hypoperfusion may induce irreversible damage in organ function and death [23][24][25] . We speculate that a global mechanism of ischemia and reperfusion may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have demonstrated that a persistent splanchnic hypoperfusion may induce irreversible damage in organ function and death [23][24][25] . We speculate that a global mechanism of ischemia and reperfusion may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…IAH is defined by a sustained or repeated pathologic elevation of IAP ≥12 mmHg (Malbrain, 2004;Malbrain et al, 2006;Saggi et al, 1998). IAH is an important cause of morbidity and mortality in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that intra-abdominal pressure (IAP) adversely affects almost all organ systems (1) and is a cause of significant morbidity and mortality (2)(3)(4)(5). Many risk factors for the development of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) have been identified in critically ill patients (6).…”
Section: Introductionmentioning
confidence: 99%